A Technique of Improved Medial Meniscus Visualization by Anterior Cruciate Ligament Graft Placement in Chronic Anterior Cruciate Deficient Knees - Vertullo, Christopher J. (Arthrosc Tech, 2016)
It is customary to perform medial meniscus repair before anterior cruciate ligament (ACL) graft placement when undertaken as a combined procedure. However, in chronic ACL-deficient knees, intraoperative anterior tibiofemoral translation can cause the medial meniscus repair to be more technically challenging. Intraoperative anterior tibiofemoral translation can both reduce the visualization of the medial meniscus and make its reduction unstable. An operative sequence alteration of ACL graft placement and tensioning before medial meniscal repair improves medial meniscus visualization in chronically ACL-deficient knees by using the ACL graft's ability to prevent anterior tibiofemoral translation. The technique sequence is as follows: (a) the medial meniscus is reduced, (b) ACL reconstruction is undertaken using a hamstring graft without final tibia fixation, (c) distal graft tension is manually applied to distal graft sutures by the surgeon to prevent tibiofemoral subluxation, (d) the medial meniscus is repaired while graft tension is applied, and (e) the graft is then fixed to the tibia using an interference screw or another device.